2007
DOI: 10.1253/circj.71.517
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Regional and Global Left Ventricular Systolic and Diastolic Function in Patients With Coronary Artery Disease Assessed by Strain Rate Imaging

Abstract: lobal left ventricular systolic and diastolic functions in patients with coronary artery disease (CAD) are traditionally assessed as important clinical and prognostic parameters. Several studies have recently demonstrated, by using non-invasive techniques including echocardiography, magnetic resonance imaging and radionuclide ventriculography, that the assessment of regional myocardial function provides important diagnostic and prognostic information in addition to that provided by global assessment alone. [1]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…During the cardiac cycle, the atria have three functions: reservoir, conduit and active contractile function. 4 Recently, several studies have shown that strain (S) and strain rates (SR) are powerful parameters of deformation; they directly reflect both global and regional systolic and diastolic myocardial function, 5 , 6 and can detect any early effects of CAD on LA functions. 7 The atrial reservoir function is reflected by systolic strain and strain rates, and the conduit and contractile functions are reflected by the early and late diastolic strain rate respectively.…”
Section: Introductionmentioning
confidence: 99%
“…During the cardiac cycle, the atria have three functions: reservoir, conduit and active contractile function. 4 Recently, several studies have shown that strain (S) and strain rates (SR) are powerful parameters of deformation; they directly reflect both global and regional systolic and diastolic myocardial function, 5 , 6 and can detect any early effects of CAD on LA functions. 7 The atrial reservoir function is reflected by systolic strain and strain rates, and the conduit and contractile functions are reflected by the early and late diastolic strain rate respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, accumulative evidence has shown that strain (ε) and strain rate (SR) are powerful echocardiographic parameters to directly reflect global and regional systolic and diastolic myocardial deformation [4][8], and to sensitively detect dysfunction from myocardial ischemia in CAD patients [9][12]. The measurement of atrial deformation by strain method is a promising and useful tool, but there are few data on the ischemia-related alterations of atrial myocardial deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of predictability of TDI leads to the suggestion that TDI would reflect primarily systolic dysfunction caused by ischemic heart diseases rather than non-ischemic diseases, although there would be a significant correlation or inter-relationship between systolic (S') and diastolic (E' and A') TDI of mitral annulus caused by the close physiologic interaction between systolic shortening and diastolic lengthening. 28,29 Similarly, in a previous study, 21 with regards to comparing the prognostic impact of echocardiographic factors against NT-ProBNP in CHF with systolic dysfunction, although it was not all the nonischemic etiology of CHF, the NT-ProBNP level provided the most informative predictor of outcome by multivariate analysis more than the E/E' ratio or restrictive filling patterns.…”
Section: Discussionmentioning
confidence: 86%